Poverty and Natural Resources in Nepal - Bhattarai, Ram Chandra (Economic Journal of Development Issues, 2010)
This paper deals about the poverty situation of the country. It reviews the available literature related on poverty and natural resources, especially forestry of the country. Literature shows that there is higher level of unemployment in urban areas and higher concentration of underemployment in rural areas. This requires the change in present education system and shift in farming practices from subsistence to commercial farming. Though the level of poverty is decreasing the inequality of income is increasing over the years due to the development activities adopted by the country. The land distribution is also highly skewed in favor of big land holders in Nepal. The share of remittance income is playing important role in the Nepalese economy. It is also playing important role for the improvement in livelihoods of rural households and helped for resilience the conflict economy. The fact on income distribution and land distribution indicate that there is strong positive relationship between income consumption and land ownership. All the issue of unequal distribution of productive assets can be addressed through proposed scientific land reform program, which ultimately may have positive impact to reduce the poverty. One of natural resources that is being used as a vehicle for the reduction of poverty is forest. Community forestry is significantly playing important role for the improvement in living standard of the people in rural areas. However, some micro level studies show that there is issue of equity in sharing the benefits from the community forests. Key words: Poverty; Inequality; Natural resources; Community forestry; Employment; Nepal Economic Journal of Development Issues Vol. 9 and 10 (2008 & 2009) Combined Issue Page: 85-101